A phenomenological-temporal perspective on inattention and hyperactivity - Daniel Victor Barbosa Magalhaes; Mathias Waldburger; Gabriel Engel Becher; André Sendra de Assis (Psicopatologia Fenomenológica Contemporânea)
The present work deals with a phenomenological analysis of the condition that contemporary psychiatry classifies as Attention Deficit Hyperactivity Disorder (ADHD). Our investigation was primarily based on understanding what would properly characterize the world experience in question for the phenomena of inattention and hyperactivity. Such experience is marked by a particular and predominantly dissonant rhythm in relation to the temporality of the most direct everyday demands, thus we argue that a desynchronization between the patient's subjective temporality and the temporal processes of their environment, based on the fact that the relationship with time is determinant in human experience, would be at the base of the phenomena of inattention and hyperactivity. Finally, we also propose a reflection on how the current socio-historical circumstances and their regimes of temporalization accentuate and demarcate this phenomenon in a particular way.